Pembudayaan Nilai Karakter Dalam Keluarga Di Desa Madwaer Kabupaten Maluku Tenggara Kec Kei Kecil Barat - Susianti Rahakbauw (Institut Agama Kristen Negeri (IAKN) Ambon, 2019)
Forming a good character for a child requires the role of a family. This writing aims to cultivate the values of the character in the family can make the children's characters better. Cultual (Enkulturasi) is the process of studying the values and cultural norms experienced by the individual during his lifetime. The beginning of the process of culture of character value for a child is individually born to know and understand his position and standing, is through the family. This research is the result of field studies using a qualitative research approach with observation and interview methods. Research location in Ohoi Madwaer, district of Kei Kecil Barat, southeast Maluku. The results showed that most parents/families have not committed their roles and responsibilities to cultivate the character values well for the child, due to busy work and other factors, parents are also rude to their children, from the results of the research is also obvious that most of the children in Ohoi Madwaer have a character that is not good, and found that there are values that are focused in applying and doing it in the family The value of religious, honest, discipline and tolerance. These values suffer from the erosion caused by unkind characters that are shown by parents and children in the family environment. Secondly, in connection with this, the value of the character has its relation to PAK, which is embedding and giving and teaching good value to everyone in order to keep the character good.Keyword: Culture, character value, family